E-book–integrated instruction as a strategy to improve students’ critical thinking skills - Purwaningsih, Kadek Dwi (Science Center Group, 2025)
Background: The rapid integration of digital technology in elementary education requires instructional strategies that not only enhance digital literacy but also promote higher-order thinking skills. E-book–integrated instruction has emerged as a promising approach to facilitate interactive, student-centered learning while supporting the development of critical thinking skills in technology-enhanced classrooms. Objective: This study aimed to examine the effectiveness of e-book–integrated instruction as a strategy to improve students’ critical thinking skills in elementary education. Methods: The study employed a quasi-experimental design with a pre-test–post-test control group structure involving 60 fifth-grade students divided into experimental and control groups. The experimental group received structured instruction using interactive e-books featuring contextual problems, multimedia elements, and reflective prompts, while the control group received conventional textbook-based instruction. Data were collected using a validated critical thinking skills assessment instrument. Statistical analyses included descriptive statistics, paired samples t-test, independent samples t-test, and normalized gain (N-Gain) analysis with a significance level of 0.05. Results: The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (p < 0.05). The experimental group demonstrated a moderate-to-high N-Gain score, indicating substantial improvement in analytical reasoning, evaluation, and problem-solving skills. In contrast, the control group showed only moderate improvement. These results confirm that structured e-book–integrated instruction effectively enhances students’ critical thinking skills. Conclusion: E-book–integrated instruction represents an effective digital learning strategy for strengthening critical thinking skills in elementary education. The integration of interactive content, contextual problem-solving tasks, and guided reflection supports meaningful cognitive engagement and promotes higher-order thinking development.